The international distribution of news the Associated Press, Press Association, and Reuters, 1848-1947 - Silberstein-Loeb, Jonathan 1981- (New York Cambridge University Press, 2014)
"Based on newly available and extensive archival evidence, this book traces the history of international news agencies and associations around the world from 1848 to 1947. Jonathan Silberstein-Loeb argues that newspaper publishers formed news associations and patronized news agencies to cut the costs of news collection and exclude competitors from gaining access to the news. In this way, cooperation facilitated the distribution of news. The extent to which state regulation permitted cooperation, or prohibited exclusivity, determined the benefit newspaper publishers derived from these organizations. This book revises our understanding of the operation and organization of the Associated Press, the BBC, the Press Association, Reuters, and the United Press. It also sheds light on the history of competition policy respecting the press, intellectual property, and the regulation of telecommunications"-- Provided by publisher.
1. Introduction -- 2. Conceiving cooperation among American newspapers, 1848-1892 -- 3. Cooperation, competition, and regulation in the United States, 1893-1945 -- 4. The 'Rationalist Illusion', the Post Office, and the Press, 1868-1913 -- 5. Private enterprise, public monopoly, and the preservation of cooperation in Britain, 1914-1941 -- 6. Reluctant imperialist?: Reuters in the British Empire, 1851-1947 -- 7. Cartel or free trade: supplying the world's news, 1856-1947 -- 8. Conclusion.
Januar Yap (Recommending faculty) : BA Mass Communication Program
Includes bibliographical references (pages 233-247) and index.
Keywords: Associated Press -- History; Press Association (Great Britain) -- History; Reuters Limited -- History; News agencies -- United States -- History; News agencies -- Great Britain -- History; Foreign news -- United States -- History; Foreign news -- Great Britain -- History; Press law -- United States; Press law -- Great Britain; BUSINESS et ECONOMICS / Economic History / bisacsh